Comparison of Fire Radiative Power Estimates From VIIRS and MODIS Observations. Issue 9 (2nd May 2018) - Li, Fangjun; Zhang, Xiaoyang; Kondragunta, Shobha; Csiszar, Ivan
Abstract: Satellite‐based active fire data are a viable tool to understand the role of global fires in the biosphere and atmosphere. The Moderate Resolution Imaging Spectroradiometer (MODIS) sensors on Aqua and Terra satellites are nearing the end of their lives. The Visible Infrared Imaging Radiometer Suite (VIIRS) sensor on the Suomi National Polar‐orbiting Partnership satellite and the subsequent Joint Polar Satellite System series is expected to extend the MODIS active fire record. Thus, understanding the similarities of and discrepancies between the two data sets during their overlap period is important for existing applications. This study investigated the dependence of the MODIS and VIIRS fire characterization capabilities on satellite view zenith angle and the relationship between the two sensors' fire radiative power (FRP) from individual fire clusters to fire data on continental and global scales. The results indicate that the VIIRS fire characterization capability is similar across swath, whereas MODIS is strongly dependent on view zenith angle. Statistical analyses reveal that the VIIRS and MODIS FRP relationship varies between different spatial scales. In fire clusters, MODIS and VIIRS FRP estimates are very comparable, except for large boreal forest fires where VIIRS FRP is approximately 47% smaller. At the continental scale, the contemporaneous FRP retrievals from MODIS and VIIRS are generally comparable and strongly correlated, but VIIRS FRP is slightly larger and their differences vary across seasons. At global 1° × 1° grids, the FRP difference between the two sensors is, on average, approximately 20% in fire‐prone regions but varies significantly in fire‐limited regions. Key Points: VIIRS mean FRP per pixel is fairly stable across swath, whereas MODIS mean FRP can increase by up to 300% at scan edge relative to nadir VIIRS FRP is generally comparable with contemporaneous MODIS FRP at continental scales and in most fire clusters FRP difference between VIIRS and MODIS retrievals is, on average, approximately 20% for 1‐degree grid cells in most fire‐prone regions